2008
DOI: 10.1211/jpp.60.1.0016
|View full text |Cite
|
Sign up to set email alerts
|

(—)-Epigallocatechin gallate (EGCG) prevents isoprenaline-induced cardiac toxicity by stabilizing cardiac marker enzymes and membrane-bound ATPases

Abstract: Intake of tea flavonoids has been reported to reduce the incidence of cardiovascular disease. The present study was undertaken to investigate the preventive effect of (-)epigallocatechin gallate (EGCG) on heart weight, cardiac marker enzymes, membrane-bound ATPases and electrolytes in isoprenaline (ISO)-induced myocardial infarcted (MI) Wistar rats. Rats subcutaneously administered ISO 100 mgkg(-1) at intervals of 24 h for 2 days resulted in significant increases in heart weight and the activities of cardiac m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…A significant increase in serum uric acid and decrease in total protein and heart vitamin E levels was observed in ISO injected rats, which is in line with the previous reports [18,21] . Large cohort studies have shown that uric acid is an important independent risk factor for cardiovascular mortality and in the development of MI.…”
Section: Discussionsupporting
confidence: 93%
“…A significant increase in serum uric acid and decrease in total protein and heart vitamin E levels was observed in ISO injected rats, which is in line with the previous reports [18,21] . Large cohort studies have shown that uric acid is an important independent risk factor for cardiovascular mortality and in the development of MI.…”
Section: Discussionsupporting
confidence: 93%
“…channel protein is known to cause increased influx of Ca 2? into myocardium following IP treatment [34]. In our study, pre-supplementation with PJ could resist to a greater extent the perturbations in Na ?…”
Section: Discussionsupporting
confidence: 49%
“…Lipid peroxidation, a type of oxidative deterioration of polyunsaturated fatty acids has been linked with altered membrane structure, and inactivation of SOD and CAT resulting in accumulation of superoxide anion, which further damages the myocardium [34]. In this context, the observed depletion in GSH and Vit C and decreased activity levels of SOD and CAT can be correlated with significant increment in cardiac LPO in IP-treated rats and indicate higher susceptibility of myocardium to oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular injury is associated with alterations in mineral homeostasis. Thus, these enzymes and ions play a vital role in the pathology of myocardial infarction [16]. Hence, we undertook the present study with new cohorts of animals to evaluate the protective effect of betaine on these membrane-bound ATPases, lipid peroxides, myocardial sulfhydryl levels, and mineral status in isoprenaline-induced myocardial infarction in rats.…”
Section: Introductionmentioning
confidence: 99%